(untitled) (Revista de Ciências Agroveterinárias, 2020)
Bacterial soft rot of garlic caused by Pseudomonas marginalis pv. marginalis is one of the crop’s main leaf diseases, and little is known about its dynamics of survival in the clove. Accordingly, this study set out to determine this bacterium’s survival in the clove with and without asepsis during storage. Garlic cloves of the Chonan cultivar were inoculated with an isolated rifampicin-resistant mutant of P. marginalis pv. marginalis to distinguish them from other bacteria and were transplanted in the field. The population present in the clove was evaluated at the end of the crop cycle and then on a monthly basis until the sixth month in storage. To quantify the bacterial population, three replications were conducted with ten grams each of cloves with and without asepsis by sodium hypochlorite for three minutes. Serial dilution was then used for isolation, followed by plating in a King B culture medium with rifampicin for selective isolation of the bacterium. After 48 hours of incubation at 28 ºC, the colonies were counted on a monthly basis to analyze their survival in the clove. The results indicate that the bacterium is unable to survive in cloves subjected to asepsis during storage, but it can survive without asepsis for up to three months.